The Effect of Teaching The Arabic Language Subject Using The "POSSEAR Strategy" on The Achievement and Reflective Thinking of Third-Grade Students in Jordan - El-Moussa, Reem Bassam; Abu Sneina, Odeh Abd Al-Gawad (Journal of Curriculum and Teaching Methodology, 2022)
The study aimed to identify the effect of teaching Arabic language using the “POSSEAR” strategy on students’ achievement and developing the skill of reflective thinking among third graders in Jordan. The experimental approach (semi-experimental design) was used, and the study’s sample consisted of (60) male and female students from third grade from Samou` elementary School in Irbid for the academic year (2021_2022). the study’s members were chosen intentionally, as they were divided into two random groups; the experimental group, numbering of (30) males and females, studied using the strategy of POSSEAR, and the control group, numbering of (30) males and females, who studied using the usual method. To achieve the aim of the study, the researcher prepared a post-assessment test and the researcher built a tool for reflective thinking. Their validity and reliability were verified and then distributed to the study’s members. The results of the study revealed that the strategy of POSSEAR affected the students’ achievement in favour of the experimental group, and it affected the development of the reflective thinking skill in the Arabic language subject and for the benefit of the experimental group. The study recommended the Ministry of Education to provide information about the strategy POSSEAR and how to apply it, and how to use activities that encourage students to practice thinking.